AKP’s Foreign Policy Regarding the Cyprus Issue: Perceptions of Turkish Cypriots - Kalaycı, Dilek (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This thesis aimed to analyse the perception of the Turkish Cypriots regarding the AKP foreign policy. Turkey has always been in relation with the European Union and in order to become a full member, Cyprus problem has been demonstrated as an obstacle for Turkey. The rise in power in 2002 by the Islamist based Western oriented party; the AKP has brought a new vision to the Turkish foreign policy. In this dissertation, it will be argued that during the Annan Plan period the AKP government has supported the plan and promoted an effort to convince the Turkish Cypriots to vote for the favour of the Plan. In other words Turkish Cypriot leaders have worked hand in hand with the AKP government in Turkey. After the failure of the Annan Plan the foreign policy of the AKP has become more conflictual, conservative and rigid. Therefore the 2009 has been the turning point of the AKP foreign policy. According to the latest developments in the island, the continuing negotiations between the two communities of Cyprus have been following by the AKP government. To be more precise, Cyprus issue has always been the national case for the all Turkish governments that has come to power. However Turkey‟s tendency to join the EU has changed the Cyprus policy of Turkey. The rise in Kurdish problem and the conflicting nature of the Middle East has pushed Turkey beyond the EU line and AKP government has decided to postpone the EU membership negotiations and leaned to become a regional power. Keywords: AKP, European Union, Annan Plan, Cyprus.

ÖZ: Bu tezin amacı Kıbrıslı Türkler‟in AKP‟nin dış politikasına olan algısını incelemektir. Türkiye‟nin AB ile ilişkileri her zaman olmuştur ve AB üyeliği için Kıbrıs sorunu hep bir engel olarak görülmüştür. 2002‟de İslam kökenli Batı yanlısı bir parti olan AKP‟nin iktidara gelmesi Türk dış politikasına yeni bir vizyon getirmiştir. Günümüzdeki gelişmelere bakıldığında adada iki toplum arasında devam eden görüşmeler AKP hükümeti tarafından takip edilmektedir. Daha açık olmak gerekirse Kıbrıs sorunu gelmiş geçmiş tüm hükümetler için milli dava olarak görülmüştür. Bunun yanında Türkiye‟nin AB‟ye katılmak için meyilli oluşu uyguladığı Kıbrıs politikasının da değişmesine sebep olmuştur. Artan Kürt meselesi ve Orta Doğu‟da baş gösteren çatışmalar nedeniyle AKP hükümetinin AB üyeliği sürecini ertelemesine ve bölgesel güç olma yolunda ilerlemesine yol açmıştır. Anahtar Kelimeler: AKP, Avrupa Birliği, Annan Planı, Kıbrıs
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2017. Supervisor: Assist. Prof. Dr. Günay Aylin Gürzel.
Keywords: Political Science and International Relations; Policy-Cyprus Problem-Justice and Development Party (AKP Ak Parti); Diplomatic Negotiations-Cyprus Problem; Cyprus-Politics and Government; Cyprus Issue-Peace Negotiations-United Nations; AKP; European Union; Annan Plan; Cyprus; Cyprus Problem; Cyprus Conflict; Cyprus Issue; Cyprus Question; Cyprus Dispute